2019
DOI: 10.1007/s00127-019-01779-7
|View full text |Cite
|
Sign up to set email alerts
|

Four-year course of quality of life and obsessive–compulsive disorder

Abstract: Objective Patients with obsessive compulsive disorder (OCD) have high disease burden. It is important to restore quality of life (QoL) in treatment, so that patients become able to live a fulfilling life. Little is known about the longitudinal course of QoL in patients with OCD, its association with remission from OCD, and about factors that contribute to an unfavourable course of QoL in remitting patients. Methods Study on the 4-year course of QoL of patients with chronic (n = 144), intermittent (n = 22), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…The mean EQ‐5D health index is within the confidence interval the EQ‐5D (0.67, 95% CI = 0.64–0.70) of large cohort of chronic and demographically comparable OCD patients (40). We did not observe an improvement in quality of life as observed in Ménchon et al This may indicate that other factors than OCD severity contributed to the quality of life outcome, or reflect the lower sensitivity and precision of the EQ‐5D‐3L in our study compared to the EQ‐5D‐5L used by Menechon et al (41) Mood improved in both responders and nonresponders, without significant between‐group differences, showing that effects of mood may be independent of effects on OCD symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…The mean EQ‐5D health index is within the confidence interval the EQ‐5D (0.67, 95% CI = 0.64–0.70) of large cohort of chronic and demographically comparable OCD patients (40). We did not observe an improvement in quality of life as observed in Ménchon et al This may indicate that other factors than OCD severity contributed to the quality of life outcome, or reflect the lower sensitivity and precision of the EQ‐5D‐3L in our study compared to the EQ‐5D‐5L used by Menechon et al (41) Mood improved in both responders and nonresponders, without significant between‐group differences, showing that effects of mood may be independent of effects on OCD symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…Here we report the results of VC/VS DBS in five patients whose comorbidities include substance use disorders, MDD, autism spectrum disorder, psychosis, anorexia nervosa, and tic disorder. A recent study of quality of life QOL in OCD demonstrated that QOL in OCD is often as dependent on the comorbid psychiatric disease as the OCD itself ( 26 ). This underscores the fact that “success” from DBS in these patients is heavily dependent on their comorbidities in addition to their OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Compulsions are defined as repeated behaviors or mental acts that patients wish to perform in response to obsessions ( 2 ). The prevalence of OCD throughout the lifetime of an individual is 1.6% and varies significantly with age ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The currently available literature suggests that the mean QoL of patients with OCD is lower than that of the healthy population. Thus, OCD has a marked impact on QoL ( 3 ).…”
Section: Introductionmentioning
confidence: 99%